Sustainable Landscape Construction: Materials and Products — Life Cycle Assessments - Gail Hansen (EDIS, 2010)
ENH1141, a 1-page fact sheet by Gail Hansen, highlights landscape construction practices that take into account sustainability at all stages of a material’s life cycle. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.